The Significance of Pragmatics: A Case in Social Communication Context - Dipta, Dinar; Virgiyanti, Diska Fatima; Fachriza, Aries; Nuraini, Eka Indah (TEKNOSASTIK, 2024)
Within a conversation, people tend to use different word choices to convey the same meaning since they consider to whom they talk. Here, pragmatics role takes place. Pragmatic study focuses on how language turns to account in social communications. Moreover, this concerns to the interrelation between the speaker and the listener. This research aims to analyse the importance of using pragmatics in social interaction and how it affects the social relation between the interpreter and the interpreted. This was a case study that performed qualitative research. The subjects were chosen considering the age-gap of both speakers and their social relationship that affects the existence of pragmatic competence. The researcher took the primary data from a conversation in social context by participating in observation and note-taking/recording technique, then the conversation was being transcribed. Meanwhile, several related literatures were used as the secondary data to maintain the reliability of the data. The data then were presented descriptively to analyse the result. It was found that pragmatics took a significance part in maintaining the social relationship for both interlocutors. The interlocutors used different level of language according to the level of language politeness. The goal of communication was not only to deliver the message among interlocutors but also to maintain a close social relationship. Furthermore, age and social status were some aspects that cannot be neglected in social norms thus the role of pragmatics was also enormously needed to perform politeness in language..